Respuestas

2012-07-24T01:09:07+02:00

1

     

          l

 

l          3                60º                   F2          

 

                                       F1

                                                     F2= K q1q2 /l2

                                                                                 F1x = ( K q1q3 /l2)cos60

                                                   F1y =( K q1q3 /l2)sen60  esta es la fuerza total vertical

Fuerza total sobre la horizontal= F2+ F1x = K q1q2 /l2 + ( K q1q3 /l2)cos60

La resultante dada como suma vectorial es =

F   =  [K q1q2 /l2 + ( K q1q3 /l2)cos60] i   +  [(K q1q3 /l2)sen60  ] (-j)